Benkangen game: Digital media in elementary school Indonesian language - Mar’atussolichah, Mar’atussolichah; Ibda, Hamidulloh; Al Hakim, Muhammad Fadloli; Faizah, Faizah; Aniqoh, Aniqoh; Mahsun, Mahsun (Journal of Education and Learning (EduLearn), 2024)
The background of this research is the need for teacher innovation in developing digital-based learning media in Indonesian language learning. The research method used is research and development (RD) with the analysis, design, develop, implement, and evaluate (ADDIE) model, which consists of five research stages: analysis, planning, development, implementation, and evaluation. Data collection techniques are questionnaires, in-depth interviews, observations, and documentation that present the results regarding innovation, features, applications, and the impact of using the benkangen game in learning Indonesian in elementary school. The subjects of this study were 25 teachers from 25 elementary schools, and 66 students from 10 elementary schools in Magelang district and Magelang city. The results showed innovation in the development of game applications based on Magelang local wisdom with game features in the form of puzzles of Magelang culture and local wisdom, Indonesian language learning materials packaged in the form of questions accompanied by the number of points in each answer, and audio that reflects local wisdom in Central Java. The novelty of this research is the development of the benkangen game based on Magelang local wisdom, which still needs to be developed by teachers in Indonesia. Future research needs to explore the innovation of Indonesian language learning games through the latest software.